Identification of mNeonGreen as a pH-Dependent, Turn-On Fluorescent Protein Sensor for Chloride - Tutol, Jasmine N. (Chembiochem, 2019)
Chloride-sensitive fluorescent proteins generated from laboratory evolution have a characteristic tyrosine residue that interacts with a chloride ion and π-stacks with the chromophore. However, the engineered yellow-green fluorescent protein mNeonGreen lacks this interaction but still binds chloride, as seen in a recently reported crystal structure. Based on its unique coordination sphere, we were curious if chloride could influence the optical properties of mNeonGreen. Here, we present the structure-guided identification and spectroscopic characterization of mNeonGreen as a turn-on fluorescent protein sensor for chloride. Our results show that chloride binding lowers the chromophore pKa and shifts the equilibrium away from the weakly fluorescent phenol form to the highly fluorescent phenolate form, resulting in a pH-dependent, turn-on fluorescence response. Moreover, through mutagenesis, we link this sensing mechanism to a non-coordinating residue in the chloride binding pocket. This discovery sets the stage to further engineer mNeonGreen as a new fluorescent protein-based tool for imaging cellular chloride.